2011
DOI: 10.1179/026708310x12683157551414
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure characterisation of solution treated (ST) and solution treated and aged (STA) Incoloy 909

Abstract: A microstructural analysis has been carried out on the commercially solution treated and aged (STA) Incoloy 909 superalloy to evaluate the phases present using optical, SEM, TEM and differential scanning calorimetry. Comparison is made where possible with non-standard STA analyses reported in the literature. In the STA condition, the main phase present besides the γ matrix was a deliberately produced Laves phase to control grain growth. Increasing the solution temperature above that recommended for the alloy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It has been previously reported in the literature that e phase (platelet) precipitates were present in the aged condition but not in commercially aged heat treatment condition. 1,[3][4][5] The previous investigation by the authors 6 did not confirm the presence of e phase in the STA condition, though there were some similar evidence to that of Guo et al, 3 showing c9 particles precipitating in a line type fashion, likely at an early stage in the transformation to the e platelets. Guo et al 3 have also concluded that when aged at higher temperatures (770uC), the e platelets precipitate directly from the supersaturated c matrix.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…It has been previously reported in the literature that e phase (platelet) precipitates were present in the aged condition but not in commercially aged heat treatment condition. 1,[3][4][5] The previous investigation by the authors 6 did not confirm the presence of e phase in the STA condition, though there were some similar evidence to that of Guo et al, 3 showing c9 particles precipitating in a line type fashion, likely at an early stage in the transformation to the e platelets. Guo et al 3 have also concluded that when aged at higher temperatures (770uC), the e platelets precipitate directly from the supersaturated c matrix.…”
Section: Resultsmentioning
confidence: 74%
“…The black grains were discussed in a previous paper by the authors, and the reader is referred to Ref. 6 for further details. Figure 2 shows a SEM image of alloy 909 in STOA condition showing the globular phase as well as copious amounts of the acicular or a platelet-like phase.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, it is very important to investigate the effect of withdrawal rates on the microstructure of nickelbase single crystal superalloys. Moreover, the multi-alloying of single crystal superalloys can lead to severe segregation in the as-cast microstructure and ultimately influences the heat treatment process and the performance of alloy [12][13][14] . In the present paper, the relationships between growth rates of the nickel-base single crystal superalloys, dendrite arm spacings (λ 1 , λ 2 ), γ' phase, γ/γ' eutectic and composition segregation were investigated.…”
mentioning
confidence: 99%